Key Limitations and New Insights Into the Toxoplasma gondii Parasite Stage Switching for Future Vaccine Development in Human, Livestock, and Cats - Mévélec, Marie-Noëlle; Lakhrif, Zineb; Dimier-Poisson, Isabelle (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasmosis is a parasitic disease affecting human, livestock and cat. Prophylactic strategies would be ideal to prevent infection. In a One Health vaccination approach, the objectives would be the prevention of congenital disease in both women and livestock, prevention/reduction of T. gondii tissue cysts in food-producing animals; and oocyst shedding in cats. Over the last few years, an explosion of strategies for vaccine development, especially due to the development of genetic-engineering technologies has emerged. The field of vaccinology has been exploring safer vaccines by the generation of recombinant immunogenic proteins, naked DNA vaccines, and viral/bacterial recombinants vectors. These strategies based on single- or few antigens, are less efficacious than recombinant live-attenuated, mostly tachyzoite T. gondii vaccine candidates. Reflections on the development of an anti-Toxoplasma vaccine must focus not only on the appropriate route of administration, capable of inducing efficient immune response, but also on the choice of the antigen (s) of interest and the associated delivery systems. To answer these questions, the choice of the animal model is essential. If mice helped in understanding the protection mechanisms, the data obtained cannot be directly transposed to humans, livestock and cats. Moreover, effectiveness vaccines should elicit strong and protective humoral and cellular immune responses at both local and systemic levels against the different stages of the parasite. Finally, challenge protocols should use the oral route, major natural route of infection, either by feeding tissue cysts or oocysts from different T. gondii strains. Effective Toxoplasma vaccines depend on our understanding of the (1) protective host immune response during T. gondii invasion and infection in the different hosts, (2) manipulation and modulation of host immune response to ensure survival of the parasites able to evade and subvert host immunity, (3) molecular mechanisms that define specific stage development. This review presents an overview of the key limitations for the development of an effective vaccine and highlights the contributions made by recent studies on the mechanisms behind stage switching to offer interesting perspectives for vaccine development.